Correlation between the oropharyngo-laryngoscopic findings and the severity of obstructive sleep apnea - Dias,Priscila Sequeira (2015)
Objective: To correlate anatomical and functional changes of the oral cavity, pharynx and larynx to the severity of obstructive sleep apnea syndrome (OSAS). Methods : We conducted a cross-sectional study of 66 patients of both genders, aged between 21 and 59 years old with complaints of snoring and / or apnea. All underwent full clinical evaluation, including physical examination, nasolarybgoscopy and polisonography. We classified individuals into groups by the value of the apnea-hypopnea index (AHI), calculated measures of association and analyzed differences by the Kruskal-Wallis and chi-square tests. Results : all patients with obesity type 2 had OSAS. We found a relationship between the uvula projection during nasoendoscopy and OSAS (OR: 4.9; p-value: 0.008; CI: 1.25-22.9). In addition, there was a major strength of association between the circular shape of the pharynx and the presence of moderate or severe OSAS (OR: 9.4, p-value: 0.002), although the CI was wide (1.80-53.13). The septal deviation and lower turbinate hypertrophy were the most frequent nasal alterations, however unrelated to gravity. Nasal obstruction was four times more common in patients without daytime sleepiness. The other craniofacial anatomical changes were not predictors for the occurrence of OSAS. Conclusion : oral, pharyngeal and laryngeal disorders participate in the pathophysiology of OSAS. The completion of the endoscopic examination is of great value to the evaluation of these patients.